Analysis of Occupational Safety and Health Management System Implementation (SMK3) at PT. PLN (Persero) UP3 South Makassar - Yunus, Pratiwi; Thamrin, Yahya; Alwi, Muh Khidri (Journal of Community Health Provision, 2025)
This research is qualitative and utilizes a descriptive approach. Data analysis techniques include data collection, data reduction, and data presentation. Three informants participated in this study: key informants, regular informants, and supporting informants. The results of this study indicate that PT PLN (Persero) UP3 Makassar Selatan has established policies related to OHS, the planning of the Occupational Safety and Health Management System has been implemented well due to the planning of procurement and construction of OHS facilities, the implementation of the OHS management system has been implemented well because the implementation of work always refers to the SOP set by the company, Measurement and Evaluation of OHS Management System is implemented well because internal monitoring and audits are always carried out by the OHS supervisor, Review and Improvement of OHS Management System has been implemented because there are always surprise inspections (sidak) carried out by the OHS supervisor to ensure the consistency of OHS implementation, and if there is a violation of procedures, sanctions will be given according to the company's internal regulations. In the implementation of the program there are obstacles, namely: the lack of human resources who are experts in the field of OHS and support related to funding. The conclusion of the implementation of OHS Management System at PT PLN (Persero) UP3 Makassar Selatan, there are several shortcomings The need for improvement in the implementation of inspections and evaluations of the implementation of the OHS Management System (SMK3) on an ongoing basis.